Ponavljanje, parodija ili raspadanje prazne ploče magijskih performativa u hrvatskome suvremenome pjesništvu - Pinter, Kornelija; Sorel, Sanjin (Wydawnictwo Naukowe UAM, 2013)
In the article, from different linguistic and literary theoretical perspectives, parodic function of anaphora is analyzed on samples of Croatian contemporary poetry. The aim is to present how a poem, especially one that is not from the contemporary lyric collection, is not a realization of „mythic time”, but in its rhythms and structures, where repetition is conditio sine qua non of lyricism, it keeps a trace, a memory of the imaginary, of the myth which in speech revives what is hidden and suppressed.
Repetition, Parody or Disintegration of the Empty Plate of Magic Performatives in Croatian Contemporary Poetry
Keywords: parody; repetition; aliteration; myth; Croatian modern poetry